2014
DOI: 10.3390/s140711416
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Fast Method for Fabrication of Endoscopic Implantable Sensor Arrays

Abstract: Here we have developed a simple method for the fabrication of disposable implantable all-solid-state ion-selective electrodes (ISE) in an array format without using complex fabrication equipment or clean room facilities. The electrodes were designed in a needle shape instead of planar electrodes for a full contact with the tissue. The needle-shape platform comprises 12 metallic pins which were functionalized with conductive inks and ISE membranes. The modified microelectrodes were characterized with cyclic vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Moreover, ISEs have been rationally designed and integrated with tailormade stretchable materials, enabling continuous monitoring in physiological fluids and cells. For example, Tahirbegi et al 48 have reported an endoscopic needle-shaped platform featuring a micro-ISE on a soft sensing microarray, enabling in situ examination of nitrate levels and pH.…”
Section: Electrochemical Sensing Techniquementioning
confidence: 99%
“…Moreover, ISEs have been rationally designed and integrated with tailormade stretchable materials, enabling continuous monitoring in physiological fluids and cells. For example, Tahirbegi et al 48 have reported an endoscopic needle-shaped platform featuring a micro-ISE on a soft sensing microarray, enabling in situ examination of nitrate levels and pH.…”
Section: Electrochemical Sensing Techniquementioning
confidence: 99%
“…Nowadays, the main development in this field and at the same time a promising scientific direction is monitoring of haemodialysis processes in real-time [ 134 ]. In this area the most remarkable are systems composed of disposable implantable all-solid-state ion-selective electrodes for endoscopic studies, which were described by Tahirbegi et al [ 135 , 136 ].…”
Section: Other Applicationsmentioning
confidence: 99%
“…The sensor may be inserted directly into the stomach by an endoscopic device indicating a possibility of an in vivo measurement with the use of an electronic tongue systems. In this way, sensor arrays may be designed for evaluation of ischemic and reperfusion states of damaged tissue [ 135 , 136 ].…”
Section: Other Applicationsmentioning
confidence: 99%
“…Many studies have focused on the recognition of taste based on the recognition of the chemical composition of the stimuli source by sensors. The electronic tongue is a type of analytical instrument that comprises an array of low-selective, nonspecific, chemical sensors and a data processing method [2], which have been applied to many fields, such as the food industry [3], water analysis [4], pharmaceutical industry [5], and clinical diagnosis [6]. Biomimetic sensors and biosensors have also been applied for taste recognition [7].…”
Section: Introductionmentioning
confidence: 99%